DETERMINACIÓN DE LA PRESENCIA DE TUBERCULOSIS BOVINA EN LA PROVINCIA DE CANTA, LIMA - Flores C., Flor (2005)
The presence of bovine tuberculosis was determined in 503 cattle older than four weeks from Canta province, Lima by the tuberculin skin test (PPD). Lecture of the test was performed 72 hours after intradermal injection. Eleven out of 503 animals (2.2%) were positive to cutaneous tuberculin stimuli. These results were analyzed by the risk evaluation technique using Monte Carlo simulation (@ Risk Program) and the probability of finding the infection in cattle from Canta province resulted greater than 1% and less than 3.2%.